Intra-Africa agricultural trade, governance quality and agricultural total factor productivity: Evidence from a panel vector autoregressive model - Delphin Kamanda Espoir; Frank Bannor; Regret Sunge (ZBW - Leibniz Information Centre for Economics, 2021)
The African Continental Free Trade Area (AfCFTA) agreement was signed by at least 54 African countries and has the potential of lifting up to 30 million Africans out of extreme poverty, according to the World Bank (2020). The agricultural sector is regarded as a fertile ground for achieving the AfCFTA ambitions. However, agricultural productivity in Africa is low and falling. It is argued that intra-Africa trade and good governance can help increase agricultural productivity. Nonetheless, both are low, casting doubt on their ability to enhance agricultural productivity. This study attempts for the first time to examine the causal relationship between the intra-Africa agricultural trade, governance quality, and the agricultural total factor productivity (ATFP) for 47 countries over the period 1995–2018. We extend the analysis to regional economic communities (RECs) to understand the diversity in this relationship within the continent. Using the panel VAR model in the generalized method of moment (GMM) estimation approach, our results suggest a long-run equilibrium relationship between the three variables. Specifically, the results indicate that at the African level, intra-Africa agricultural trade has a statistically positive effect on governance quality and ATFP. In contrast, good governance has positive and negative impacts on ATFP and trade, respectively. We also find that ATFP positively influences intra-Africa agricultural trade and governance. At the RECs level, our estimations show significant heterogeneity in the three variables' impacts. Based on our findings, we recommend a rapid implementation of the AfCFTA agreement. However, we suggest that the implementation should be idiosyncratic to each region's structural economies. Furthermore, we encourage the promotion of good governance, particularly in agriculture policy implementation.
Keywords: C23; G38; O47; Q17; 330; Agricultural trade; agricultural total factor productivity; governance; PVAR